2016
DOI: 10.1016/j.fertnstert.2015.12.131
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproductive technology and risk of adverse obstetric outcomes in dichorionic twin pregnancies: a systematic review and meta-analysis

Abstract: The rates of placenta previa, elective cesarean section, preterm birth, very preterm birth, low birth weight, and congenital malformations were significantly higher in dichorionic twin pregnancies after ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 62 publications
5
79
0
4
Order By: Relevance
“…In all meta-analytic data [16, 17, 22, 23] perinatal mortality was not increased. A recent cohort study [24], however, reported an adjusted risk of perinatal death for twins 45 and 85 % lower among ART births than fertile or subfertile births, respectively.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In all meta-analytic data [16, 17, 22, 23] perinatal mortality was not increased. A recent cohort study [24], however, reported an adjusted risk of perinatal death for twins 45 and 85 % lower among ART births than fertile or subfertile births, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…To this regard, a recent meta-analysis [23] including 15 cohort studies and involving 6,420 dichorionic twins after ART and 13,650 dichorionic NC twins confirmed a risk of placenta previa (RR 2.99, 95 % CI 1.51 to 5.92), PTB (RR 1.13, 95 % CI 1.00 to 1.29), VPTB (RR 1.39, 95 % CI 1.07 to 1.82), LBW (RR 1.11, 95 % CI 1.00 to 1.23), and elective cesarean sections (RR 1.79, 95 % CI 1.49 to 2.16) significantly increased in ART pregnancies. Very recently, a nationwide registry based study demonstrated in women who conceived dizygotic twins after IVF/ICSI rates of PIH lower than after NC (aOR 0.74, 95 % CI 0.66 to 0.83) [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If whether or not twin pregnancies constitute an undesirable outcome of IVF were to be the sole question, the answer would be simple: Following IVF or natural conception, twin pregnancies are, indeed, best avoided 1519. Ours, after all, is a mono-ovulatory uniparous species that is ill-suited to concurrent multiple progeny 20.…”
Section: Yes: Twins Constitute An Adverse Outcome Of Ivfmentioning
confidence: 99%
“…These pregnancies have great maternal and fetal risks due to many complications that occur during or after the course of pregnancy [2] [3].…”
Section: Introductionmentioning
confidence: 99%